Muller muscle conjunctival resection or external levator advancement; a quantitative comparison of symmetry in unilateral ptosis * - Cabuk, Kubra Serefoglu; Nacaroglu, Senay Asik; Karabulut, Gamze Ozturk; Fazil, Korhan; Arslan, Mehmet Selcuk; Guler, Mehmet Guray; Taskapili, Muhittin (SAGE PUBLICATIONS LTD, 2022)
Purpose To compare muller muscle conjunctival resection (MMCR) and external levator advancement (ELA) in terms of objective and subjective symmetry in unilateral ptosis. Methods The patients who underwent unilateral MMCR (group1, n = 25) and ELA (group2, n = 25) were reviewed retrospectively. With the written algorithm, margin reflex distance-1 (MRD1), localization of the contour peak, and the percentage of overlapping curvatures (POC) of both upper eyelid curves were calculated. Semi-automated measurements were compared with the manual measurements. The correlation between objective and subjective symmetry was evaluated. Results Preoperative levator functions were similar in both groups (13.93 +/- 3.25 mm and 13.3 +/- 2.86 mm, respectively). We found strong correlations between manual and semi-automated measurements (ICC: 0.942, 95% CI = 0.924-0.956, p < 0.001). Preoperative MRD1 (2.15 +/- 0.90 vs 1.51 +/- 1.01, p = 0.022) and POC was lower in group 2 (66% vs 47.2%, p = 0.01). In the postoperative period, the increase in MRD1 and POC were similar in both groups (p = 0.2 and p = 0.7 respectively), and the contour peak displaced temporally (p < 0.01) providing a symmetric peak in both groups. Subjective symmetry increased as the difference in MRD1 between two eyes decreased (r = -0.456, p = 0.001), and POC increased (r = 0.396, p = 0.004). Conclusions Besides subjective symmetry, MMCR and ELA are equally effective in ensuring symmetry objectively, as measured with MRD1 and contour peak symmetry and POC in unilateral ptosis. POC may be used as a criterion of symmetry in the evaluation of ptosis.
Keywords: Bezier curve; levator advancement; mullerectomy; symmetry; UPPER EYELID CONTOUR; LID CONTOUR; BLEPHAROPTOSIS; TARSECTOMY; AGREEMENT; OUTCOMES; DISEASE; Ophthalmology